GATA2 deficiency detected by newborn screening for SCID: A case report - Escobar Vasco, Alejandra; Broglie, Larisa; Talano, Julie-An; Routes, John; Verbsky, James; Remiker, Allison (Frontiers in Pediatrics, 2023)
The early diagnosis and treatment of inborn errors of immunity (IEI) is crucial in reducing the morbidity and mortality due to these disorders. The institution of newborn screening (NBS) for the diagnosis of Severe Combined Immune Deficiency (SCID) has decreased the mortality of this disorder and led to the discovery of novel genetic defects that cause this disease. GATA2 deficiency is an autosomal dominant, pleiotropic disease with clinical manifestations that include bone marrow failure, monocyte and B cell deficiency, leukemia, pulmonary alveolar proteinosis and lymphedema. We present the case of an infant identified by newborn screening for SCID due to GATA2 deficiency.